Synthesis And Characterization Of Nanocomposite: 2-4-Dichlorophenoxy Acetate-Zinc-Aluminium Hydrotalcitelike Layers - Mohd Amin, Junainah (2003)
A direct intercalation of 2,4-dichlorophenoxyacetate (2,4-D) into Zn-Al-Iayered double hydroxide (ZAL) was carried out by spontaneous self-assembly technique to produce Zn- AI-2,4-D nanocomposite (ZAD). The aging process was done by conventional and microwave-assisted methods. For both methods, the results showed that the intercalation process resulted in the expansion of the interlayer spacing from 10.7 A in ZAL to around 19.0 - 24.6 A in ZAD. Sharp and intense peaks for 003 and 006 reflections indicate wellordered layered structure which exhibit some common features of layered materials, e.g. narrow, symmetrical and strong peaks at low 20values and weaker, less symmetric peaks at higher 20 values. Further characterization of the resulting materials including organicinorganic content, surface area and porosity, thermal analysis and morphology, were also carried out.